Convergence in alcohol abuse in Brazilian capitals between genders, 2006 to 2019: what population surveys show - Deborah Carvalho Malta; Alanna Gomes da Silva; Elton Junio Sady Prates; Francielle Thalita Almeida Alves; Elier Broche Cristo; Ísis Eloah Machado (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objective: To analyze the temporal trend of the prevalence of alcohol abuse among adults in Brazilian capitals, between 2006 and 2019. Methods: Time series study, based on data from the Surveillance System for Risk and Protective Factors for Chronic Diseases by Telephone Survey (Vigitel), between 2006 and 2019. The population consisted of adults (≥ 18 years old) with landline telephone residing in Brazilian capitals. The trend analysis was performed by linear regression. Results: Between 2006 and 2019 there was a significant increase (p = 0.03) in the abusive consumption of alcoholic beverages in the total adult population, from 15.6 to 18.8%. Among men, there was a stability trend (p = 0.96), and among women, there was an increase from 7.7 to 13.3% (p < 0.001; β = 0.295). In the male gender stratified by capitals, from 2006 to 2019 there was a reduction in Belém, Fortaleza, João Pessoa, Macapá, Manaus, Natal, Recife, São Luis, and Teresina. On the other hand, there was growth in the Federal District. Among women, the trend was upward in: Aracaju, Belo Horizonte, Cuiabá, Curitiba, Florianópolis, Goiânia, Palmas, Porto Alegre, Rio de Janeiro, Salvador, São Paulo, Vitória, and the Federal District. Conclusion: The results indicate that more adult women are currently drinking in excess compared to previous years, suggesting an increased risk of alcohol-related harm in this portion of the population in Brazilian capitals, bringing about a convergence effect with the prevalence among men and women.